Design of Crotoxin-Based Peptides with Potentiator Activity Targeting the ΔF508NBD1 Cystic Fibrosis Transmembrane Conductance Regulator. Issue 3 (1st February 2023) - Ravatin, Marc; Odolczyk, Norbert; Servel, Nathalie; Guijarro, J. Iñaki; Tagat, Eric; Chevalier, Benoit; Baatallah, Nesrine; Corringer, Pierre-Jean; Lukács, Gergely L.; Edelman, Aleksander; Zielenkiewicz, Piotr; Chambard, Jean-Marie; et al.
Graphical abstract: Highlights: Design of CB-derived peptides based on the CB/ΔF508CFTR binding interface. CB-derived peptides target the ΔF508NBD1 domain of mutated CFTR. Novel potentiator peptides increase ΔF508CFTR chloride channel current. The identified potentiators offer a promising therapeutic strategy for cystic fibrosis. Abstract: We have previously shown that the CBb subunit of crotoxin, a β-neurotoxin with phospholipase A2 (PLA2 ) activity, targets the human ΔF508CFTR chloride channel implicated in cystic fibrosis (CF). By direct binding to the nucleotide binding domain 1 (NBD1) of ΔF508CFTR, this neurotoxic PLA2 acts as a potentiator increasing chloride channel current and corrects the trafficking defect of misfolded ΔF508CFTR inside the cell. Here, for a therapeutics development of new anti-cystic fibrosis agents, we use a structure-based in silico approach to design peptides mimicking the CBb-ΔF508NBD1 interface. Combining biophysical and electrophysiological methods, we identify several peptides that interact with the ΔF508NBD1 domain and reveal their effects as potentiators on phosphorylated ΔF508CFTR. Moreover, protein-peptide interactions and electrophysiological studies allowed us to identify key residues of ΔF508NBD1 governing the interactions with the novel potentiators. The designed peptides bind to the same region as CBb phospholipase A2 on ΔF508NBD1 and potentiate chloride channel activity. Certain peptides also show an additive effect towards the clinically approved VX-770 potentiator. The identified CF therapeutics peptides represent a novel class of CFTR potentiators and illustrate a strategy leading to reproducing the effect of specific protein–protein interactions.